2012
DOI: 10.2147/ijn.s29334
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular entry of nanoparticles via serum sensitive clathrin-mediated endocytosis, and plasma membrane permeabilization

Abstract: Increasing production and application of nanomaterials raises significant questions regarding the potential for cellular entry and toxicity of nanoparticles. It was observed that the presence of serum reduces the cellular association of 20 nm carboxylate-modified fluorescent polystyrene beads up to 20-fold, relative to cells incubated in serum-free media. Analysis by confocal microscopy demonstrated that the presence of serum greatly reduces the cell surface association of nanoparticles, as well as the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…This is in accordance with other results investigating the time and concentration dependence of uptake for a variety of NPs (e.g. polystyrene and gold) and cell lines (Johnston et al 2010;Trono et al 2011;Smith et al 2012;Mazzolini et al 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with other results investigating the time and concentration dependence of uptake for a variety of NPs (e.g. polystyrene and gold) and cell lines (Johnston et al 2010;Trono et al 2011;Smith et al 2012;Mazzolini et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The NPs are known to interact with molecules at the cell surface, and can subsequently be internalized specifically through membrane interactions, via receptor-ligand mediated active processes or electrostatic interactions, or through nonspecific routes such as passive fluid encapsulation within vesicles during internalization processes. A series of calculations were performed to determine the potential for uptake through direct membrane interaction versus uptake due to passive incorporation into vesicles in the liquid phase (Smith et al 2012).…”
Section: Mechanism Of Uptake: Membrane-bound or Fluid Phase?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies have demonstrated that the physicochemical properties of a nanocarrier modulates its intracellular trafficking, 55,56 it still remained unclear, prior to our current study, as to how the presence of multiple copies of a targeting ligand on the surface of a nanocarrier, i.e. its multivalency, influences its intracellular trafficking and subcellular accumulation, relative to its non-targeted counterpart, or even relative to the targeting ligand alone.…”
Section: Resultsmentioning
confidence: 96%
“…Immediately before transfection, media were aspirated and replaced with 100 μl Opti-MEM + 2% FBS. The serum concentration was 2% FBS for the transfection experiments because low serum conditions increases cell uptake and minimizes the introduction of experimental variability due to rapid cell proliferation 24 . Fresh or reconstituted lyophilized polyplexes containing 150 ng pDNA were then added to each well.…”
Section: Methodsmentioning
confidence: 99%